Academic Writing and Politics - Bhandari, Laxman Prasad; Pokharel, Prem Raj (Lumbini Journal of Language and Literature, 2022)
Writers challenge the governing traditions and values, beliefs, and interests, so they can take a stand against injustice. Academic writing plays a vital role in the discursive construction and maintenance of the hegemony of the dominant class. The paper purposed to explore the link between academic writing and politics. Thus, we explore how academic writing empowers authors to influence various aspects of their lives using library research method in this paper. Applying Gramsci’s social theory, we discuss the relationship between academic writing and politics under four themes: writing in the global context, politics of academic language, writing and ideology, and the power of writing. The findings suggest that academic writing is connected with power, politics, and ideologies to influence and control others through intellectual and moral unity along with the accord of economic and political power. This paper also concludes that academic writing enhances people to organize the multitude of social beliefs about good or bad, or acceptable or unacceptable for them to bring change in their lives.